Design of self-adaptive spatio-temporal diversity joint scheduling strategy - Qing TONG; Yunfei GUO; Shumin HUO; Yawen WANG; Yujia MAN; Kai ZHANG (Tongxin xuebao)
To solve the problem that a diversity system is difficult to take defense capability, defense cost and quality of service into account at the same time under a single diversity strategy, firstly, the scheduling object selecting sequences under different security levels were constructed based on the measurement of scheduling heterogeneity, executor security and spatial diversity.Then, according to the coarse-grained evaluation of threat environment, the scheduling time and scheduling object were determined comprehensively.Through the realization of the spatio-temporal diversity Web server system in a cloud environment, the proposed scheduling strategy was tested with attack and defense experiments and compared with the existing scheduling strategies.The results show that the proposed scheduling strategy improves the defense capability significantly and maintains a high quality of service within the acceptable defense cost increasing range.